Radiation therapy induced intestinal barrier damage and repair process - differences in salivary metabolites and monitoring of intestinal barrier function - Jingjing, Zhang; Kun, Wang; Yanyu, Qiao; Mengjie, Zhang; Yunqing, Chen; Yulong, Tian; Xuelong, Jiao; Xiaojie, Tan; Haitao, Jiang; Feng, Hou (Frontiers in Immunology, 2025)
PurposeColorectal cancer (CRC) is still one of the most common malignant tumors, with gradual increase in its annual morbidity and mortality. But most cases are diagnosed in the late stage. For stage II-III cancer, clinical guidelines recommend surgery following neoadjuvant radiation therapy at ≥6 weeks after the last radiotherapy is completed. However, radiotherapy may impair intestinal mucosal barrier function, especially the biological and immune barriers, accompanied by perioperative complications. This study was conducted to investigate the changes, repair patterns, and potential mechanisms in patients after radiotherapy.MethodsThis study detected inflammatory factors in postoperative intestinal mucosal tissue and serum, as well as metabolites in saliva samples, and collected hematoxylin-eosin (HE)-stained pathological images in CRC patients who had received and did not receive radiotherapy.ResultsThe results showed that after radiotherapy, there were significantly impaired intestinal mucosal tissue structure; obviously elevated inflammatory factors in intestinal mucosal tissue and blood; as well as upregulation/downregulation of metabolites in saliva samples.ConclusionIn conclusion, findings in this study may provide potential reference for predicting the recovery of intestinal mucosa and selecting the optimal timing for surgery after radiotherapy. In addition, this study will benefit the understanding and reduction of perioperative complications caused by intestinal barrier damage.